A pecuária na produção do espaço agrário de Simão Dias (SE) - Santos, Angleide Silva de Mendonça (2005)
This study aimed to analyze the importance of cattle-breeding in the production of agrarian region of Simão Dias in Sergipe state, evaluating its role in formation and transformation of State, the changes succeed because modernization of agriculture and the State s and financial investments role as agents which transform the space. The methodology was composed by bibliographical, cartographical and statistical surveys, as researches in the empirical field, through directed interviews with farmer and also the recognition of the particular reality to this space. The results had reaffirmed cattle-breeding as an important agricultural activity in the town, being present since the big producers, as main activity, until family agriculture, which is a complementary activity to farming and establishes a reservation of values. The agrarian structure is concentrated and there is predominance of pastures in the use of lands, as a consequence of cattle-breeding. The agricultural activity is fulfilled with modernization signs, with predominance of pastures, racial progress, sanitary treatments, and introduction of ostrich breeding enterprise molds and grains production with use of improved seeds and the accomplishment of the agricultural area. State government has participated in the process of modernization not only bringing financial investments to the sector but also in the dissemination of modern techniques. Several agents involved in the productive chain make of this activity a great generator of jobs and incomes for the municipal economy.